A COMPARISON OF SOLID-PHASE EXTRACTION METHODS FOR BISPHENOL A IN CHEESE SAMPLES - Kürekci, Cemil; Tan, Sait; Arslan, Ali; Özgen, Sara Betül; Sakın, Fatıh (My University, 2021)
In this study, four different solid phase extraction (SPE) methods were compared for the determination of bisphenol A (BPA) in cheese samples using HPLC-FD. All methods were validated according to the parameters; linearity, recovery, precision, detection and quantification limits (LOD-LOQ). Subsequently, BPA levels were determined in twenty cheese samples commercially available in Elazığ province. All the extraction methods showed good performances for quantitative analysis of PBA, achieving very low LOD (0.16-0.39 ?g/kg) and LOQ (0.53-1.30 ?g/ kg) values. The average fortification recoveries for spiked BPA (3-30 ?g/kg) ranged between 93.1 and 100.8%. 55% of cheese samples had BPA concentration ranging from 0.75 ?g/kg to 8.46 ?g/kg and estimated daily intake (EDI) was measured as 0,001 ?g/kg BW per day. On the basis of EDI, the consumption of cheese itself cannot be considered as significant health problem, but results impose a systematic monitoring of dairy products.
Keywords: HPLC; Bisphenol A; cheese; Solid-phase extraction